Reducing bacterial contamination in an Orthopedic Theatre ventilated by natural ventilation, in a Developing Country - Stephanie Thomas; Rish Palmer; Edward Phillipo; Geoffrey Chipungu (Journal of Infection in Developing Countries)
Introduction: All surgical procedures have the potential for infection and some of the main sources are contamination from airborne particles, theatre personnel and the theatre environment.  There is strong evidence that the use of ultra-clean air flow systems in orthopedic operating theatres reduces the incidence of deep sepsis after surgery. In the developing world however, this is often an unrealistic solution. The aim of this study was to establish baseline levels of contamination in a working orthopedic theatre, at the Queen Elizabeth Central Hospital, Blantyre, Malawi. To feedback results to the theatre team, promote infection prevention discussion and work with the team to implement workable and realistic goals to improve the intra-operative environment. Methodology: Samples were collected from theatre equipment available at the time of surgery, from theatre water and theatre air using passive air sampling techniques. Samples were immediately transferred to the Central Microbiology Laboratory for culture on basic culture media. Results: Bacterial contamination of theatre equipment, intra-operative theatre air and water was detected. Results were discussed with the theatre and infection prevention team who were receptive to feedback with regards to infection prevention strategies and keen to develop simple measures which could be put in place to change practice. Conclusions: In this setting, we suggest that implementing workable and realistic goals such as, establishing baseline rates of bacterial contamination and introduction of strict protocols for asepsis and theatre etiquette, may reduce bacterial contamination rates and subsequent intra-operative infection in the absence of expensive engineering solutions.